Notes from a field hospital south of Mosul - John M. Quinn V; Omar F. Amouri; Pete Reed (BMC, 2018)
Abstract This short letter from the field is offered as a rapid communiqué of the emergency medical situation in Mosul and surrounding areas on the eve of the final onslaught to liberate the city. This letter is based on emergency medical work at two World Health Organization (WHO) and Ministry of Health (MoH) Iraq lead Role II+ Field Hospital facilities south of Mosul City from April to June 2017; these facilities are currently and temporarily managed and administered by private medical industry until full handover to MoH Iraq, with WHO support and expert facilitation. The prominence of non-state actors in the conflict, using hybrid warfare tactics that maximize casualties, makes health security a particular challenge for the global community. This challenge requires health leaders and other actors in the region to set clear strategic goals that support public health of the many millions displaced, maimed and affected by the war. Whether in clinical medicine, development, peace and stability operations, or global health diplomacy, the shared values and conviction to best serve vulnerable communities and mitigate morbidity must embrace the lessons of evidenced based practice derived from military medical experience. WHO is leading the charge in disaster response for the conflict in Iraq, and many challenges remain. This might also include developing a new process in emergency medical response that utilizes private contracting to improve efficiency in delivery and overall sustainability.